The Knowledge Level and The Obedience of Maternal in Undertaking HIV Test - Rochmayanti, Ucik; Ernawati, Ernawati; Ismoedijanto, Ismoedijanto (Health Notions, 2018)
Based on the data of Surabaya City Health Office, in 2015 there were 30% of PITC from 55800 maternal and 37 of them were found HIV positive. This percentage has not had obvious explanation. This motivates the researcher to conduct the research entitled â The Correlation Between the Knowledge and the Obedience of Maternal  in Undertaking HIV Testâ.This was analytic observational research by aaplying Cross sectional  in 3 different  community health centre (puskesmas) with high HIV rates. They are community health centre Dupak, Jagir, and East Perak Surabaya. Data collecting technique was Systematic Random Sampling and Rules of Thumb. The number of  pregnant mother was 80 that undertook ANC in those community health centre. The result shows that 90% of pregnant mother have good knowledge characteristic level. Statistic test used cramers v calculator  shows that the knowledge p< 0,05 which mean knowledge level has correlation with the obedience of undertaking HIV test. This research conluded that knowledge level has correlation with the obedience of undertaking HIV test.